2013
DOI: 10.1177/0266242613503178
|View full text |Cite
|
Sign up to set email alerts
|

The impact of size on small and medium-sized enterprise public sector tendering

Abstract: Small and medium-sized enterprise (SME) involvement in the marketplace for public sector contracts has been the subject of scholarly interest for some time. Studies undertaken to date have largely concentrated on SME resource disadvantage relative to large firms in competing for and winning public sector contracts. Much less attention has been paid to disadvantage within the SME population and how factors such as size, sector and owner characteristics affect SME tendering. In response, this paper examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 59 publications
4
82
1
3
Order By: Relevance
“…Analysis of SMEs' reported experiences by size, age, and tendering experience was also undertaken. Previous research by Flynn et al (2013a), Karjalainen and Kemppainen (2008) and Pickernell et al (2011) has found SME size to be a significant predictor of tendering behaviour and outcomes. Firm age and tendering experience have also been linked to tendering outcomes (GHK, 2010).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Analysis of SMEs' reported experiences by size, age, and tendering experience was also undertaken. Previous research by Flynn et al (2013a), Karjalainen and Kemppainen (2008) and Pickernell et al (2011) has found SME size to be a significant predictor of tendering behaviour and outcomes. Firm age and tendering experience have also been linked to tendering outcomes (GHK, 2010).…”
Section: Resultsmentioning
confidence: 84%
“…Finally, a reassessment of generic SME-friendly policy is advisable in light of the finding that micro-enterprises seem to benefiting less from its implementation than larger SMEs. SMEs are a heterogeneous group when it comes to public sector tendering and policy should reflect this fact (Flynn et al 2013a;Karjalainen and Kemppainen, 2008). The findings presented here raise challenging questions for all those with an interest in making public procurement more conducive to SME participation.…”
Section: Discussionmentioning
confidence: 89%
“…Studies that have examined the relationship between the size of firms and public sector tendering showed that "size, measured by employee number, significantly influences small and medium-sized enterprises' (SMEs) tendering resources, behaviour and success" (Flynn, McKevitt and Davis, 2013). Karjalainen and Kemppainen (2008) examined how availability of resources as perceived by companies influence SME involvement in the bidding process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interest in SMEs stems from the fact that about 98 percent of companies in the EU are SMEs (corresponding to the share of SMEs in the total number of Croatian companies as well 4 ), and because of the policy goal to increase SMEs' involvement as public suppliers. In assessing business attitudes towards the public procurement system, this research builds on the empirical literature regarding the company size, and adds the supplier business sector as an underexplored but possibly significant characteristic of respondents (Flynn, McKevitt and Davis, 2013). The model also differentiates between principal contractor and subcontractors as shown in Figure 1.…”
Section: Modelmentioning
confidence: 99%
“…An analysis of the experiences of SMEs supplying the publicly funded UK heritage sector carried out by Loader and Norton (2015) 10 demonstrates that the heritage sector has distinct characteristics that affect the public procurement of traditional building skills. The impact of size on small-and medium-sized enterprise public sector tendering by Flynn et al (2015) 11 indicates that SMEs are heterogeneous tenderers, and point to the need for more focused research on how SME characteristics influence ability and willingness to tender. There is considerable debate about using so-called public-private partnership (PPP) in PP projects.…”
Section: Introductionmentioning
confidence: 99%